2020
DOI: 10.22226/2410-3535-2020-3-283-287
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio modeling of dynamic stability of silicon prismanes

Abstract: We present the results of a study on the dynamic stability of silabiprismanes by means of the density functional theory. Silabiprismanes present an elementary case of a particular type of silicon nanotubes with an extremely small cross-section, constructed from dehydrogenated molecules of cyclosilanes (silicon rings). Unlike higher polysilaprismanes, they are formed by only three silicon rings and described by the chemical formula (Si n) 3 H 2n. In the presented study, we limited ourselves to the cases n = 5 ÷… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Silicon analogs of the prismanes are also extensively studied in the literature. [19][20][21][22][23][24][25][26] To date, only the simplest silaprismanes, such as Si 6 H 6 , have been synthesized, 19 and the properties of the other analogs are predicted with theoretical studies. [20][21][22][23][24][25][26][27] It has been reported that substituting carbon atoms with silicon atoms stabilizes the prismane framework.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Silicon analogs of the prismanes are also extensively studied in the literature. [19][20][21][22][23][24][25][26] To date, only the simplest silaprismanes, such as Si 6 H 6 , have been synthesized, 19 and the properties of the other analogs are predicted with theoretical studies. [20][21][22][23][24][25][26][27] It has been reported that substituting carbon atoms with silicon atoms stabilizes the prismane framework.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26] To date, only the simplest silaprismanes, such as Si 6 H 6 , have been synthesized, 19 and the properties of the other analogs are predicted with theoretical studies. [20][21][22][23][24][25][26][27] It has been reported that substituting carbon atoms with silicon atoms stabilizes the prismane framework. 22 In a recent computational study, it was observed that the kinetic stability of Si 18 H 12 is higher than that of its carbon analog (C 18 H 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation